Kampanye Isi Piringku untuk Kejadian Stunting pada Balita - Gita Adelia; Dini Maulinda; Sri Widya Ningsih; Fitri Dyna; Angga Arfina; Eka Malfasari (STIKes Payung Negeri Pekanbaru, 2022)
Introduction: Stunting is a chronic malnutrition problem that causes growth disorders, namely the child's height is lower or shorter (short) than the standard age. One of the current government focuses is stunting prevention by promoting the “Fill My Plate” Campaign. Objective: to determine the relationship between mother's knowledge about the